2020
DOI: 10.7454/jki.v0i0.1233
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Peer-Assisted Learning in Nursing Student Knowledge and Compliance in The Application of Standard Precautions

Abstract: The learning process in higher nursing education develops student competences, such as applying standard precautions, in providing professional nursing care. To improve student knowledge and compliance related to standard precautions requires innovation from lecturers in providing appropriate learning methods. Peer-assisted learning (PAL) can enhance the active role of students and improve achievement. The PAL method involves senior students as peer teachers who help junior students. Using a questionnaire as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The simulation education with and without SP has reported greater improvements in knowledge compared to the usual PRP or lecture education [ 50 , 51 ]. Regarding PRP, our findings are similar to the results of previous studies showing that the method of peer-assisted learning is useful for improving the knowledge about standard precautions [ 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…The simulation education with and without SP has reported greater improvements in knowledge compared to the usual PRP or lecture education [ 50 , 51 ]. Regarding PRP, our findings are similar to the results of previous studies showing that the method of peer-assisted learning is useful for improving the knowledge about standard precautions [ 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…There was a statistically significant difference in favor of peer mentoring group in their awareness of standardized precautions and infection control performance levels after the intervention. Furthermore, Desnita and Surya (2020) conducted a study in which the results showed that infection control performance was significantly higher in the peer mentoring group. This was also, similarly, to a study made by Marey et al (2020) which revealed that there was a high statistically significant improvement in nurses' levels of total performance in all items of infection control post peer mentoring program.…”
Section: Discussionmentioning
confidence: 99%